2016
DOI: 10.5551/jat.32698
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ-glutamyltransferase and Mortality due to Cardiovascular Disease in Japanese Men and Women

Abstract: Aim:Whether the association between serum -glutamyltransferase ( -GTP) levels and total cardiovascular disease (CVD) mortality is independent of alcohol drinking in East Asian populations is not well known. We conducted a pooled analysis of Japanese men and women that enabled an analysis restricted to never-drinkers. Methods: A total of 15,987 men and 25,053 women aged 40-79 years, pooled from seven cohort studies throughout Japan, were followed-up to examine sex-specific relationship between serum -GTP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…GGT has been used as a sensitive biomarker of alcohol consumption as well as hepatic inflammation and NAFLD. Subgroup analysis exhibited a persistent association of GGT with CVD and mortality independent of alcohol consumption, consistent with the results of previous studies 3 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…GGT has been used as a sensitive biomarker of alcohol consumption as well as hepatic inflammation and NAFLD. Subgroup analysis exhibited a persistent association of GGT with CVD and mortality independent of alcohol consumption, consistent with the results of previous studies 3 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…We found greater CRF clustering associated with the higher odds ratio for higher serum GGT levels in both genders, especially for men. Many cohort studies have also shown that GGT may be a risk factor for total CVD mortality 35 and that serum GGT activity may be an independent predictive marker of CVD, cardiac death, and cardiac transplantation 36 , 37 . Further studies are needed to confirm our findings and elucidate the exact mechanisms between GGT levels and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here are consistent with these studies. [8][9][10] A major limitation of this study is the cross-sectional design. Of notice, the small sample size was limited to the definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%